Catalyst for Fenton reaction by using iron tailings to bear Fe < 2 + > as well as preparation method and application of catalyst
By preparing a porous sheet catalyst and using iron tailings to carry Fe2+ and PMMA microspheres, the problem of traditional catalyst recovery and low degradation efficiency is solved, and the organic pollutants in wastewater are efficiently degraded and the treatment effect is economical and environmentally friendly.
Patent Information
- Application Number
- CN202411654513.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional Fenton reaction catalysts are difficult to separate and recover from the aqueous phase after the reaction, resulting in increased treatment costs and difficult to effectively degrade organic pollutants in wastewater.
Through the technical steps such as acid solution, crushing, sintering, and other technical steps, it is prepared to carry FE2+with FE2+as the core porous tablets, and PMMA micro -balls are used as pore makers to form a porous structure with high contact area.
It achieves efficient recycling of catalysts, significantly improves the degradation efficiency of dissolved organic pollutants, reduces treatment costs, and has good economic and environmental benefits.
Smart Images

Figure CN119346112A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid waste resource utilization and wastewater treatment generated by ore dressing, and in particular to a method for treating solid waste by using iron tailings to carry Fe 2+ Catalyst for Fenton reaction and preparation method and application thereof. Background Art
[0002] With the rapid development of my country's mineral industry, the amount of iron tailings produced by ore dressing plants is huge, and a large amount of mining solid waste is piled up, which not only occupies a large amount of land resources, but also causes potential pollution and safety risks to the environment. Therefore, the comprehensive utilization of iron tailings has become an important way to achieve sustainable development of mineral resources. Through technological innovation, the utilization efficiency of iron tailings can be effectively improved, environmental pollution can be reduced, and the coordinated development of economy and environment can be promoted.
[0003] The treatment of organic pollutants in wastewater is an important topic in the current field of environmental engineering. With the rapid development of industrialization and urbanization, the types and quantities of organic pollutants in wastewater are increasing. These pollutants are often difficult to degrade, posing a threat to the environment and human health. As an advanced oxidation technology, the Fenton reaction has been widely studied and applied in wastewater treatment, especially in the degradation of organic pollutants. Traditional Fenton reaction catalysts are difficult to separate and recover from the aqueous phase after the reaction, resulting in increased treatment costs. Therefore, research and development is needed to improve the recovery rate of catalysts. Summary of the invention
[0004] In view of the above problems, the present invention aims to provide a method for carrying Fe 2+ Catalyst for Fenton reaction and its preparation method and application. The method is to prepare a catalyst with Fe supported by iron tailings through acid hydrolysis, tableting and sintering reduction. 2+ The catalyst used for the Fenton reaction not only utilizes iron tailings waste, but also solves the problem of iron tailings solid waste accumulation to a certain extent. At the same time, the catalyst with a porous structure is formed by using iron tailings as a Fenton reaction catalyst carrier and PMMA microspheres as a pore-forming agent, which has better performance and utilization rate in degrading organic pollutants in wastewater.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for carrying Fe by iron tailings 2+ The preparation method of the catalyst for Fenton reaction comprises the following steps:
[0007] Step 1: Preparation of iron ore tailings powder
[0008] Grinding the iron tailings to obtain iron tailings powder; placing the ground iron tailings powder in a beaker, adding an acid dissolving agent to completely immerse the iron tailings powder, and letting it stand; then centrifugally washing the acid-treated iron tailings powder and drying it;
[0009] Step 2: Make your own cobalt ferrite powder
[0010] Using ferric nitrate nonahydrate and cobalt nitrate hexahydrate as raw materials, dissolving the raw materials in deionized water, stirring and adding ammonia water, adjusting the pH value, continuing to stir, adding the stirred liquid into a reactor, and performing a hydrothermal reaction; after cooling, centrifugation washing and drying are performed to obtain black-red cobalt ferrite powder;
[0011] Step 3: Mixing and grinding raw materials for catalyst preparation
[0012] Preparation of iron tailings loaded with Fe 2+ The raw materials for the Fenton reaction catalyst include: the iron tailings powder prepared in step 1, the self-made cobalt ferrite powder in step 2, and a pore-forming agent. The raw materials are weighed and mixed, and a binder is added, and the powder is fully ground until it has a certain viscosity;
[0013] Step 4: Tableting and debonding
[0014] The powder with a certain viscosity in step 3 is dry pressed to obtain a green embryo and then subjected to binder removal;
[0015] Step 5: Reduction sintering
[0016] The green embryo after debinding in step 4 is placed in a tubular furnace, and after heating and heat preservation treatment in a mixed gas atmosphere of hydrogen and argon, it is cooled to room temperature with the furnace to obtain the Fe2O3-supported ... 2+ A catalyst for Fenton reaction, wherein the catalyst is in the form of a porous sheet.
[0017] In the step 1, the acidolysis agent is 3 mol / L hydrochloric acid, and the standing time is 12 h;
[0018] The speed of centrifugal washing was 6000 r / min, the time was 2 min, and washing was performed three times with alcohol and deionized water respectively;
[0019] The drying temperature of the drying treatment is 60°C and the drying time is 6h.
[0020] In step 2, the chemical reaction principle of the homemade cobalt ferrite is as follows:
[0021] Fe(NO 3 ) 3 9H 2 0+3NH 3 ·H 2 O→Fe(OH)3 ↓+3NH 4 NO 3 +9H 2 0
[0022] Co(NO 3 ) 2 6H 2 O+2NH 3 ·H 2 O→Co(OH) 2 ↓+2NH 4 NO 3 +6H 2 O
[0023]
[0024] In step 2, the pH value is adjusted to pH=10, the stirring time is 20 min, the hydrothermal reaction temperature is 180° C., and the reaction time is 4 h;
[0025] The speed of centrifugal washing was 8000 r / min, the time was 3 min, and washing was performed three times with alcohol and deionized water respectively;
[0026] The drying temperature of the drying treatment is 60°C and the drying time is 6h.
[0027] The content of each component in the raw material of step 3 is 80.24-85.56wt.% of the iron tailings powder after acid treatment, 13.44wt.% of the homemade cobalt ferrite, and 1.00-6.33wt.% of the pore-forming agent;
[0028] The pore-forming agent is PMMA microspheres;
[0029] The adhesive is a polyvinyl alcohol adhesive.
[0030] In step 4, the dry pressing is performed by punching with upper and lower dies, the pressing pressure is 2.7-3.0 MPa, and the holding time is 2-3 min.
[0031] In step 4, debinding means placing the green embryo in a muffle furnace, heating it to 500° C. at a heating rate of 2° C. / min, and keeping it warm for 4 hours.
[0032] The heating rate of the heating treatment in step 5 is 5°C / min;
[0033] The insulation temperature of the insulation treatment is 1150° C. and the insulation time is 4 hours.
[0034] The present invention also provides a Fe-supported Fe tailings prepared according to the above preparation method. 2+ Catalysts for the Fenton reaction.
[0035] The present invention also provides the method of using iron tailings to carry Fe 2+ Application of catalysts for Fenton reaction in organic wastewater treatment.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) After the iron tailings are treated by acid hydrolysis, the iron tailings powder, cobalt ferrite powder and PMMA microspheres are directly mixed, pressed and sintered by atmosphere to form Fe 2+ The catalyst is loaded on the iron tailings to form a porous sheet catalyst. The catalyst and hydrogen peroxide are placed in the sewage to generate OH - The porous structure can provide a larger contact area and better performance, and can degrade dissolved organic pollutants faster and more effectively.
[0038] (2) Compared with the traditional catalysts in the Fenton reaction, the catalyst used in the present invention uses cheap iron tailings as a carrier, PMMA microspheres as a pore-forming agent, and a simple mixing-tableting-atmosphere sintering technology. The raw materials are widely available and inexpensive, the preparation method is simple to operate, and it is easier to recycle and reuse. Therefore, the catalyst prepared by the present invention has obvious economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a SEM image of the catalyst for Fenton reaction in Example 1 of the present invention;
[0040] Figure 2 is the XRD pattern of the self-made cobalt ferrite in Example 1 of the present invention;
[0041] Figure 3A This is a comparison diagram of ultraviolet light absorption after methyl orange is degraded for 36 hours by Application Example 1 of the present invention and Comparative Application Example 1;
[0042] Figure 3B This is a comparison chart of ultraviolet light absorption after Rhodamine B was degraded for 36 hours between Application Example 1 of the present invention and Comparative Application Example 1;
[0043] Figure 3C This is a comparison diagram of ultraviolet light absorption after methylene blue is degraded for 36 hours by Application Example 1 of the present invention and Comparative Application Example 1;
[0044] Figure 4A This is a comparison chart of ultraviolet absorption of methyl orange after 36 hours of degradation of methyl orange by Application Example 1 of the present invention and Comparative Application Example 2 and a blank control;
[0045] Figure 4B It is a comparative diagram of ultraviolet absorption of Rhodamine B after 36 hours of degradation of Rhodamine B by Application Example 1 of the present invention and Comparative Application Example 2 and blank control Rhodamine B;
[0046] Figure 4C It is a comparison chart of ultraviolet absorption of methylene blue after 36 hours of degradation of methylene blue by Application Example 1 of the present invention and Comparative Application Example 2 and blank control methylene blue;
[0047] Figure 5A This is a comparison chart of ultraviolet absorption of methyl orange after 36 hours of degradation of methyl orange by Application Example 2 of the present invention and Comparative Application Example 2 and blank control methyl orange;
[0048] Figure 5B It is a comparison chart of ultraviolet absorption of Rhodamine B after 36 hours of degradation of Rhodamine B by Application Example 2 of the present invention and Comparative Application Example 2 and blank control Rhodamine B;
[0049] Figure 5C It is a comparison chart of ultraviolet absorption of methylene blue after 36 hours of degradation of methylene blue by Application Example 2 of the present invention and Comparative Application Example 2 and blank control methylene blue;
[0050] Fig. 6A This is a comparison chart of ultraviolet absorption of methyl orange after 36 hours of degradation of methyl orange by Application Example 3 of the present invention and Comparative Application Example 2 and a blank control methyl orange;
[0051] Figure 6B It is a comparative diagram of ultraviolet absorption of Rhodamine B after 36 hours of degradation of Rhodamine B by Application Example 3 of the present invention and Comparative Application Example 2 and blank control Rhodamine B;
[0052] Figure 6C It is a comparison chart of ultraviolet absorption of methylene blue after 36 hours of degradation of methylene blue by Application Example 3 of the present invention and Comparative Application Example 2 and blank control methylene blue;
[0053] Figure 7 This is a comparative diagram of ultraviolet light absorption when Application Example 1 of the present invention degrades methyl orange for 60 min, 120 min, and 180 min;
[0054] Figure 8 This is a comparative diagram of ultraviolet light absorption when Rhodamine B is degraded for 60min, 120min, and 180min in Application Example 1 of the present invention;
[0055] Fig. 9 This is a comparative diagram of ultraviolet light absorption when methylene blue is degraded for 60 min, 120 min and 180 min in Application Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with specific implementation methods.
[0057] Example 1
[0058] This embodiment provides a method of using iron tailings to carry Fe 2+ The method for preparing a catalyst for Fenton reaction comprises the following steps:
[0059] Step 1: Preparation of iron ore tailings powder
[0060] Grinding: Grind 5 g of iron tailings to obtain iron tailings powder;
[0061] Acid hydrolysis: Place the ground iron tailings in a beaker, add 3 mol / L hydrochloric acid until it is completely submerged, and let it stand for 12 hours;
[0062] Washing and drying: The iron tailings powder after acid hydrolysis was washed three times with alcohol and deionized water at 6000r / min centrifugation for 2 minutes. After washing, it was placed in an oven at 60°C for drying for 6 hours.
[0063] Step 2: Make your own cobalt ferrite powder
[0064] Weigh 6.464g of ferric nitrate nine hydrate and 2.328g of cobalt nitrate hexahydrate into a beaker, add 240mL of deionized water, stir until completely dissolved, add ammonia water, adjust to pH=10, and continue stirring for 20min; put the stirred liquid into a reactor for hydrothermal reaction at 180°C for 4h; after cooling, wash three times with deionized water and respectively at 8000r / min for 3min, after washing, place in an oven at 60°C for drying for 6h; obtain blackish red cobalt ferrite powder, Figure 2 Shown is the XRD pattern of the cobalt ferrite powder.
[0065] Step 3: Mixing and grinding raw materials for catalyst preparation
[0066] Weigh 0.75g of the iron tailings powder prepared in step 1, 0.121g of the cobalt ferrite powder prepared in step 2 and 0.029g of PMMA microspheres and mix them, i.e. 83.33wt.% of the acid-treated iron tailings powder, 13.44wt.% of the homemade cobalt ferrite powder, and 3.22wt.% of the PMMA microspheres, and then add 3 drops of 5wt.% polyvinyl alcohol adhesive and grind them thoroughly.
[0067] Step 4: Tableting and debonding
[0068] Tableting: Weigh 0.3 g of the raw materials mixed and ground in step 3, and use upper and lower dies to punch each other, maintain the pressure at 2.7-3.0 MPa for 2-3 minutes, and perform dry pressing to obtain a green embryo;
[0069] Debinding: Place the green embryo in a muffle furnace and heat it to 500℃ at a heating rate of 2℃ / min, and keep it warm for 4h.
[0070] Step 5: Reduction sintering
[0071] The sample after debinding was placed in a tube furnace, and the temperature was raised to 1150℃ at a rate of 5℃ / min and kept at this temperature for 4h. After cooling in the furnace, the Fe2O3-loaded iron tailings were obtained. 2+ Catalysts for Fenton reactions, Figure 1 Shown is a SEM image of the porous sheet catalyst.
[0072] Example 2
[0073] This embodiment provides a method of using iron tailings to carry Fe 2+ The method for preparing a catalyst for Fenton reaction comprises the following steps:
[0074] Step 1: Preparation of iron ore tailings powder
[0075] Grinding: Grind 5 g of iron tailings to obtain iron tailings powder;
[0076] Acid hydrolysis: Place the ground iron tailings in a beaker, add 3 mol / L hydrochloric acid until it is completely submerged, and let it stand for 12 hours;
[0077] Washing and drying: The iron tailings powder after acid hydrolysis was washed three times with alcohol and deionized water at 6000r / min centrifugation for 2 minutes. After washing, it was placed in an oven at 60°C for drying for 6 hours.
[0078] Step 2: Make your own cobalt ferrite powder
[0079] Weigh 6.464g of ferric nitrate nonahydrate and 2.328g of cobalt nitrate hexahydrate into a beaker, add 240mL of deionized water, stir until completely dissolved, add ammonia water, adjust to pH=10, and continue stirring for 20min; put the stirred liquid into a reactor for hydrothermal reaction at 180°C for 4h; after cooling, wash three times with deionized water and respectively at 8000r / min for 3min, after washing, place in an oven at 60°C for drying for 6h; obtain blackish red cobalt ferrite powder.
[0080] Step 3: Mixing and grinding raw materials for catalyst preparation
[0081] Weigh 0.723g of acid-treated iron tailings powder, 0.121g of cobalt ferrite powder and 0.057g of PMMA microspheres and mix them, i.e. 80.24wt.% of acid-treated iron tailings powder, 13.44wt.% of homemade cobalt ferrite powder, 6.33wt.% of PMMA microspheres, then add 3 drops of 5wt.% polyvinyl alcohol adhesive and grind them thoroughly.
[0082] Step 4: Tableting and debonding
[0083] Tableting: Weigh 0.3 g of the raw materials mixed and ground in step 3, and use upper and lower dies to punch each other, maintain the pressure at 2.7-3.0 MPa for 2-3 minutes, and perform dry pressing to obtain a green embryo;
[0084] Debinding: Place the green embryo in a muffle furnace and heat it to 500℃ at a heating rate of 2℃ / min, and keep it warm for 4h.
[0085] Step 5: Reduction sintering
[0086] The sample after debinding was placed in a tube furnace, and argon / hydrogen mixed gas was introduced. The temperature was raised to 1150℃ at a heating rate of 5℃ / min and kept at this temperature for 4h. After cooling in the furnace, the Fe2O3-loaded iron tailings were obtained. 2+ Catalysts for the Fenton reaction.
[0087] Example 3
[0088] This embodiment provides a method of using iron tailings to carry Fe 2+ The method for preparing a catalyst for Fenton reaction comprises the following steps:
[0089] Step 1: Preparation of iron ore tailings powder
[0090] Grinding: Grind 5 g of iron tailings to obtain iron tailings powder;
[0091] Acid hydrolysis: Place the ground iron tailings in a beaker, add 3 mol / L hydrochloric acid until it is completely submerged, and let it stand for 12 hours;
[0092] Washing and drying: The iron tailings powder after acid hydrolysis was washed three times with alcohol and deionized water at 6000r / min centrifugation for 2 minutes. After washing, it was placed in an oven at 60°C for drying for 6 hours.
[0093] Step 2: Make your own cobalt ferrite powder
[0094] Weigh 6.464g of ferric nitrate nonahydrate and 2.328g of cobalt nitrate hexahydrate into a beaker, add 240mL of deionized water, stir until completely dissolved, add ammonia water, adjust to pH = 10, and continue stirring for 20 minutes; put the stirred liquid into a reactor for hydrothermal reaction at 180°C for 4 hours; after cooling, wash three times with deionized water and respectively at 8000r / min for 3 minutes. After washing, place in an oven at 60°C for drying for 6 hours to obtain blackish red cobalt ferrite powder.
[0095] Step 3: Mixing and grinding raw materials for catalyst preparation
[0096] Weigh 0.770g of acid-treated iron tailings powder, 0.121g of cobalt ferrite powder and 0.009g of PMMA microspheres and mix them, i.e. 85.56wt.% of acid-treated iron tailings powder, 13.44wt.% of homemade cobalt ferrite powder, 1.00wt.% of PMMA microspheres, then add 3 drops of 5wt.% polyvinyl alcohol adhesive and grind them thoroughly.
[0097] Step 4: Tableting and debonding
[0098] Tableting: Weigh 0.3 g of the raw materials mixed and ground in step 3, and use upper and lower dies to punch each other, maintain the pressure at 2.7-3.0 MPa for 2-3 minutes, and perform dry pressing to obtain a green embryo;
[0099] Debinding: Place the green embryo in a muffle furnace and heat it to 500℃ at a heating rate of 2℃ / min, and keep it warm for 4h.
[0100] Step 5: Reduction sintering
[0101] The sample after debinding was placed in a tube furnace, and argon / hydrogen mixed gas was introduced. The temperature was raised to 1150℃ at a heating rate of 5℃ / min and kept at this temperature for 4h. After cooling in the furnace, the Fe2O3-loaded iron tailings were obtained. 2+ Catalysts for the Fenton reaction.
[0102] In order to further verify the catalytic effect of the embodiment of the present invention for the Fenton reaction catalyst, the present invention also provides a comparative example, an application example and a comparative application example of the catalyst.
[0103] Comparative Example 1
[0104] Except that the pore-forming agent PMMA microspheres are not added in the step of mixing and grinding the raw materials used to prepare the catalyst, the remaining steps are the same as the preparation method of Example 1, as shown in detail as follows:
[0105] Step 3: Mixing and grinding raw materials for catalyst preparation
[0106] Weigh 0.779 g of acid-treated iron tailings powder and 0.121 g of cobalt ferrite powder and mix them, i.e. 86.56 wt. % of acid-treated iron tailings powder and 13.44 wt. % of homemade cobalt ferrite powder, then add 3 drops of 5 wt. % polyvinyl alcohol binder and grind them thoroughly.
[0107] Application Example 1
[0108] An application of using the catalyst in Example 1 to perform Fenton reaction to degrade methyl orange, rhodamine B, and methylene blue, comprising the following steps:
[0109] 5 mL of methyl orange solution with a concentration of 70 ppm, rhodamine B solution with a concentration of 70 ppm, and methylene blue solution with a concentration of 30 ppm were measured and placed in three glass bottles, 5 mL of 5 wt.% hydrogen peroxide solution was added to each of the three bottles for mixing, and then a piece of the catalyst prepared in Example 1 was placed in each of the three bottles;
[0110] Start timing, and after 36 hours of reaction, take samples to test the degradation of methyl orange, rhodamine B, and methylene blue.
[0111] Application Example 2
[0112] An application of using the catalyst in Example 2 to perform Fenton reaction to degrade methyl orange, rhodamine B, and methylene blue comprises the following steps:
[0113] 5 mL of methyl orange with a concentration of 70 ppm, rhodamine B with a concentration of 70 ppm, and methylene blue solution with a concentration of 30 ppm were measured and placed in three glass bottles, 5 mL of 5 wt.% hydrogen peroxide solution was added to each of the three bottles for mixing, and then a piece of the catalyst prepared in Example 2 was placed in each of the three bottles;
[0114] Start timing, and after 36 hours of reaction, take samples to test the degradation of methyl orange, rhodamine B, and methylene blue.
[0115] Application Example 3
[0116] An application of using the catalyst in Example 3 to perform Fenton reaction to degrade methyl orange, rhodamine B, and methylene blue comprises the following steps:
[0117] 5 mL of 70 ppm methyl orange, 70 ppm rhodamine B and 30 ppm methylene blue solution were measured and placed in three glass bottles, 5 mL of 5 wt.% hydrogen peroxide solution was added to each of the three bottles, and then a piece of the catalyst prepared in Example 3 was placed in each of the three bottles;
[0118] Start timing, and after 36 hours of reaction, take samples to test the degradation of methyl orange, rhodamine B, and methylene blue.
[0119] Application Example 4
[0120] An application of using the catalyst in Example 1 to perform Fenton reaction to degrade methyl orange over time, comprising the following steps:
[0121] 5 mL of 70 ppm methyl orange solution was measured and placed in a glass bottle, 5 mL of 10 wt.% hydrogen peroxide solution was added and mixed, and then a piece of the catalyst prepared in Example 1 was placed in the glass bottle;
[0122] Start timing and test the degradation of methyl orange after 60 min, 120 min, and 180 min of reaction.
[0123] Application Example 5
[0124] An application of using the catalyst in Example 1 to perform Fenton reaction to degrade Rhodamine B over time, comprising the following steps:
[0125] 5 mL of a 70 ppm Rhodamine B solution was measured and placed in a glass bottle, 5 mL of a 10 wt.% hydrogen peroxide solution was added and mixed, and then a piece of the catalyst prepared in Example 1 was placed in the glass bottle;
[0126] Start timing and test the degradation of Rhodamine B after 60 min, 120 min, and 180 min of reaction.
[0127] Application Example 6
[0128] An application of using the catalyst in Example 1 to perform Fenton reaction to degrade methylene blue over time, comprising the following steps:
[0129] 5 mL of a 30 ppm methylene blue solution was measured and placed in a glass bottle, 5 mL of a 10 wt.% hydrogen peroxide solution was added and mixed, and then a piece of the catalyst prepared in Example 1 was placed in the glass bottle;
[0130] Start timing and test the degradation of Rhodamine B after 60 min, 120 min, and 180 min of reaction.
[0131] Comparative application example 1
[0132] The difference between this comparative application example and application example 1 is that the Fe2O3-loaded iron tailings in comparative example 1 is used. 2+ Flake catalyst for Fenton reaction.
[0133] Comparative Application Example 2
[0134] The difference between this comparative application example and application example 1 is that only hydrogen peroxide is used to degrade methyl orange, rhodamine B, and methylene blue, and the steps include:
[0135] 5 mL of 70 ppm methyl orange solution, 70 ppm rhodamine B solution and 30 ppm methylene blue solution were measured and placed in three glass bottles, and 5 mL of 5 wt.% hydrogen peroxide solution was added to each of the bottles for mixing.
[0136] Catalytic effect test
[0137] In order to further analyze the catalytic effect of the catalyst:
[0138] In Application Examples 1, 2, and 3, the catalysts in Example 1, Example 2, and Example 3 were used, respectively, and hydrogen peroxide was added to degrade methyl orange, rhodamine B, and methylene blue. After 36 hours of reaction, 350 μl of the sample was taken, and the sampled solution was diluted 5 times. The obtained solution was analyzed for the degradation of methyl orange, rhodamine B, and methylene blue using an ultraviolet spectrophotometer.
[0139] In comparative application example 1, the catalyst in comparative example 1 was used, hydrogen peroxide was added, and methyl orange, rhodamine B, and methylene blue were degraded. After 36 hours of reaction, 350 μl of the sample was taken, and the sampled solution was diluted 5 times. The obtained solution was analyzed by ultraviolet spectrophotometer for the degradation of methyl orange, rhodamine B, and methylene blue.
[0140] In comparative application example 2, only hydrogen peroxide was used to degrade methyl orange, rhodamine B, and methylene blue. After 36 hours of reaction, 350 μl of the sample was taken and the sample solution was diluted 5 times. The obtained solution was analyzed by an ultraviolet spectrophotometer for the absorption of ultraviolet light after degradation of methyl orange, rhodamine B, and methylene blue.
[0141] In Application Examples 4, 5, and 6, the catalyst in Example 1 was applied to the Fenton reaction to degrade methyl orange, rhodamine B, and methylene blue, respectively. At 60 min, 120 min, and 180 min of the reaction, 350 μl of the sample was taken at a predetermined time point, and the sampled solution was diluted 5 times. The obtained solution was analyzed for the degradation of methyl orange, rhodamine B, and methylene blue using an ultraviolet spectrophotometer.
[0142] The removal effect of methyl orange can be found in Figure 3A , Figure 4A , Figure 5A , Fig. 6A and Figure 7 , Figure 3A The comparison of the ultraviolet absorption of methyl orange after the catalyst of Application Example 1 and Comparative Application Example 1 degraded methyl orange for 36 hours; Figure 4A The comparison of the ultraviolet absorption of methyl orange after methyl orange was degraded by the catalyst of Application Example 1 and Comparative Application Example 2 for 36 hours; Figure 5A The comparison of the ultraviolet absorption of methyl orange after methyl orange was degraded by the catalyst of Application Example 2 and Comparative Application Example 2 for 36 hours; Fig. 6A The comparison of the ultraviolet absorption of methyl orange after methyl orange was degraded by the catalyst of application example 3 and the catalyst of comparative application example 2 for 36 hours; Figure 7 The ultraviolet absorption of methyl orange when the catalyst in Application Example 1 degrades methyl orange for 60 minutes, 120 minutes, and 180 minutes;
[0143] The removal effect of rhodamine B can be found in Figure 3B , Figure 4B , Figure 5B , Figure 6B and Figure 8 , Figure 3B The comparison of the ultraviolet absorption of Rhodamine B after the catalyst of Application Example 1 and Comparative Application Example 1 degraded Rhodamine B for 36 hours; Figure 4B The comparison of the ultraviolet absorption of Rhodamine B after the catalyst of Application Example 1 and Comparative Application Example 2 degraded Rhodamine B for 36 hours; Figure 5B The comparison of the ultraviolet absorption of Rhodamine B after the catalyst of Application Example 2 and Comparative Application Example 2 degraded Rhodamine B for 36 hours; Figure 6B The comparison of the ultraviolet absorption of Rhodamine B after the catalyst of Application Example 3 and Comparative Application Example 2 degraded Rhodamine B for 36 hours; Figure 8 It is the absorption of ultraviolet light by Rhodamine B when the catalyst in Application Example 1 degrades Rhodamine B for 60 min, 120 min and 180 min.
[0144] The removal effect of methylene blue can be seen in Figure 3C , Figure 4C , Figure 5C , Figure 6C and Fig. 9 , Figure 3C The comparison of the ultraviolet absorption of methylene blue after the catalyst of Application Example 1 and Comparative Application Example 1 degraded methylene blue for 36 hours; Figure 4C The comparison of the ultraviolet absorption of methylene blue after the catalyst of application example 1 and the catalyst of comparative application example 2 degraded methylene blue for 36 hours; Figure 5C The comparison of the ultraviolet absorption of methylene blue after the catalyst of Application Example 2 and Comparative Application Example 2 degraded methylene blue for 36 hours; Figure 6C The comparison of the ultraviolet absorption of methylene blue after the catalyst of Application Example 3 and Comparative Application Example 2 degraded methylene blue for 36 hours; Fig. 9 It is the absorption of ultraviolet light by methylene blue when the catalyst in Application Example 1 is used to degrade methylene blue for 60 min, 120 min and 180 min.
[0145] from Figure 3A , Figure 3B , Figure 3C It can be seen that after the Fenton reaction degradation using the catalyst of Example 1, less ultraviolet light is absorbed and the concentration is lower. By comparison, it is further shown that using PMMA microspheres as a pore-forming agent promotes the formation of a porous structure, so that the prepared porous sheet catalyst has better catalytic performance.
[0146] from Figures 4A-4C , Figures 5A-5C , Figures 6A-6CIt can be seen that the catalysts of Examples 1, 2, and 3 absorb less ultraviolet light and have a lower concentration after Fenton reaction degradation, which further indicates that the porous sheet catalyst prepared by the present invention has good catalytic performance.
[0147] from Figure 7 , Figure 8 , Fig. 9 It can be seen that when the catalyst in Example 1 is used to degrade methyl orange, rhodamine B and methylene blue, the absorption peak decreases with the increase of time. In this process, the height of the absorption peak decreases at each time interval is relatively balanced, further indicating that the catalytic effect of the catalyst of the present invention lasts for a long time and has stable performance.
[0148] The above embodiment of the present invention discloses a method of using iron tailings to carry Fe 2+ The catalyst for Fenton reaction, its preparation method and application are introduced in detail. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any combination or equivalent transformation made on the basis of the above embodiments belongs to the protection scope of the present invention.
Claims
1. A method of using iron tailings to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: The steps include: Step 1: Preparation of iron ore tailings powder Grinding the iron tailings to obtain iron tailings powder; placing the ground iron tailings powder in a beaker, adding an acid dissolving agent to completely immerse the iron tailings powder, and letting it stand; then centrifugally washing the acid-treated iron tailings powder and drying it; Step 2: Make your own cobalt ferrite powder Using ferric nitrate nonahydrate and cobalt nitrate hexahydrate as raw materials, dissolving the raw materials in deionized water, stirring and adding ammonia water, adjusting the pH value, continuing to stir, adding the stirred liquid into a reactor, and performing a hydrothermal reaction; after cooling, centrifugation washing and drying are performed to obtain black-red cobalt ferrite powder; Step 3: Mixing and grinding raw materials for catalyst preparation Preparation of iron tailings loaded with Fe 2+ The raw materials for the Fenton reaction catalyst include: the iron tailings powder prepared in step 1, the self-made cobalt ferrite powder in step 2, and a pore-forming agent. The raw materials are weighed and mixed, and a binder is added and fully ground until the powder has viscosity. Step 4: Tableting and debonding The viscous powder in step 3 is dry pressed to obtain a green embryo and then subjected to binder removal; Step 5: Reduction sintering The green embryo after debinding in step 4 is placed in a tubular furnace, and after heating and heat preservation treatment in a mixed gas atmosphere of hydrogen and argon, it is cooled to room temperature with the furnace to obtain the Fe2O3-supported ... 2+ A catalyst for Fenton reaction, wherein the catalyst is in the form of a porous sheet.
2. The method of claim 1 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: In the step 1, the acidolysis agent is 3 mol / L hydrochloric acid; and the rotation speed of the centrifugal washing is 6000 r / min.
3. The method of claim 1 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: In step 2, the chemical reaction principle of the homemade cobalt ferrite is as follows: Fe(NO3)3·9H20+3NH3·H2O→Fe(OH)3↓+3NH4NO3+9H20 Co(NO3)2·6H2O+2NH3·H2O→Co(OH)2↓+2NH4NO3+6H2O 4. The method of claim 1 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: In step 2, the pH value is adjusted to pH=10, the hydrothermal reaction temperature is 180° C., and the reaction time is 4 hours; the rotation speed of the centrifugal washing is 8000 r / min.
5. The method of claim 1 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: The content of each component in the raw material of step 3 is 80.24-85.56wt.% of the iron tailings powder after acid treatment, 13.44wt.% of the homemade cobalt ferrite, and 1.00-6.33wt.% of the pore-forming agent; The pore-forming agent is PMMA microspheres; The adhesive is a polyvinyl alcohol adhesive.
6. The method of claim 1 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: In step 4, the dry pressing is performed by punching with upper and lower dies, the pressing pressure is 2.7-3.0 MPa, and the holding time is 2-3 min.
7. The method of claim 1 or 5 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: In step 4, debinding means placing the green embryo in a muffle furnace, heating it to 500° C. at a heating rate of 2° C. / min, and keeping it warm for 4 hours.
8. The method of claim 1 wherein the iron tailings are used to carry Fe 2+ The method for preparing a catalyst for Fenton reaction is characterized in that: The heating rate of the heating treatment in step 5 is 5°C / min; The insulation temperature of the insulation treatment is 1150° C. and the insulation time is 4 hours.
9. A method of using iron tailings to carry Fe 2+ A catalyst for Fenton reaction, characterized in that Using the method of claim 1 to carry Fe 2+ The invention relates to a catalyst for Fenton reaction.
10. The method of claim 9 wherein the iron tailings are used to carry Fe 2+ Application of catalysts for Fenton reaction in organic wastewater treatment.